Analisis Hukum Pemberian Remisi Terhadap Narapidana di Lembaga Pemasyarakatan Klas II A Binjai - Sastro, Heru Prabowo Adi; Marlina, Marlina; Eddy, Triono; Nasution, Aulia Rosa (ARBITER: Jurnal Ilmiah Magister Hukum, 2019)
The study was conducted to determine the Supervision of Remission Against Prisoners in Class II A Binjai Penitentiary. The nature of the study is normative juridical. Literature and document study material is used as the main material while field data will be used as supporting or supplementary data. The collected data is sorted and analyzed judicially and qualitative data are interpreted logically systematically by deductive and inductive methods. The results showed that the implementation of remission to prisoners experienced a shift both from the understanding, criteria, and objectives. According to the provisions, the original remission was the right of prisoners, shifted into a kind of gift given by the government, and finally shifted to an arena of buying and selling interests. As a result of this shift, there has been a blurring of the legal rules for granting remissions that automatically impacted their supervision. In addition, the implementation of remission is a prisoner's right and also as a stimulus so that prisoners are willing to undergo coaching to change behavior in accordance with the objectives of the Penal System. The supervisory system for remission in Penitentiary involves Penal Institutions which starts from the Penitentiary Technical Implementation Unit, Regional Office of the Ministry of Justice and Human Rights to be forwarded to the Directorate General of Corrections, also involving Supervising Judges and Observers.